2015
DOI: 10.1016/j.addr.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of miRNAs in the pathogenesis, diagnosis and therapy of pancreatic cancer

Abstract: Despite considerable progress being made in understanding pancreatic cancer (PC) pathogenesis, it still remains the 10th most often diagnosed malignancy in the world and 4th leading cause of cancer related deaths in the United States with a five year survival rate of only 6%. The aggressive nature, lack of early diagnostic and prognostic markers, late clinical presentation, and limited efficacy of existing treatment regimens makes PC a lethal cancer with high mortality and poor prognosis. Therefore, novel reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 280 publications
2
69
0
Order By: Relevance
“…Sensitive and specific biomarkers to identify patients with pancreatic cancer at an early stage are needed [2123]. This study describes 2 novel panels of miRNAs for diagnosing pancreatic cancer using the combination of 3 or 6 miRNAs in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive and specific biomarkers to identify patients with pancreatic cancer at an early stage are needed [2123]. This study describes 2 novel panels of miRNAs for diagnosing pancreatic cancer using the combination of 3 or 6 miRNAs in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…There are also some studies demonstrating that a number of miRNAs are aberrantly expressed in pancreatic cancer cells/tissues and involved in the regulation of many pancreatic cancer related genes [1727]. Therefore, investigation of novel miRNA regulatory pathways may offer insights into identification of new pancreatic oncotargets and development of new therapeutics [7, 28, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…[4] MiRNAs are small (19-24 nucleotides) noncoding RNAs playing an important gene-regulatory role in the post-transcriptional phase. [5] Several studies have identified key miRNAs involved in tumor development and progression [6] Importantly, miRNAs are stable in body fluids, [7] either in secreted microvesicles or bound to carrier proteins. This offers a unique opportunity to exploit miRNAs as potential biomarkers for early detection of various cancers, including PDAC.…”
mentioning
confidence: 99%